Back to the capitalist future: Fantasy and the paradox of crisis. Issue 2 (14th March 2016) - Bloom, Peter
Abstract : This paper draws on a Lacanian perspective to better understand how crisis can paradoxically produce fantasies of ideological renewal. Using the 2008 economic meltdown as an example, it argues that these events are articulated as a part of a crisis narrative that links past ideals with future stability and progress. At the level of subjectivity, these fantasies reflect the psychological trauma individuals feel in the face of encountering the incoherent and fragmentary 'Real' of their identity during periods of greater social and economic upheaval. In the context of the current crisis, political leaders attempted to reinforce capitalist ideologies through promoting a fantasy of recovery that connected future prosperity with values of financialization and a global 'free market', as is borne out in their public statements following this event. Critically, this points to the importance of 'traversing' these fantasies in order to break free from desires for renewal in favour of those emphasizing transformation.